Ten coaching tips for high school athletics during the COVID-19 pandemic - Filiz, B.; Konukman, F.; Karaca, Y.; Tufekcioglu, E. (Strategies, 2021)
High school sports play a vital role in students` lives. These sports are closely linked to participation in extracurricular activities, higher grade point av erages, higher levels of participation, and fewer discipline problems. Given that schools and sports clubs are closed in most countries due to COVID-19, it is more vital than ever for coaches to stay connected with athletes. The measures taken to reduce the spreading rate of the epidemic, the prolongation of stay at home orders, social isolation and quarantine processes have caused disrup tion to sports activities for young athletes. While the ath letes tried to stay in shape while under quarantine condi tions, they had to plan their training programs according to these current conditions. Additionally, sports competitions that were canceled or postponed have caused athletes to be deprived of resources that strengthen their social cohesion, contribute to their emotional excitement and enable them to do more physical activity (United Nations, 2020). As a result, COVID-19 disrupted the order of sports activities and prevented the expected productivity from these activi ties (FIFA, 2020)